Upper-molar intrusion using anterior palatal anchorage and the 'Mini-Mousetrap' appliance - Wilmes Benedict; Niegel Thomas; Drescher Dieter (Sciendo, 2018)
The intrusion of over-erupted upper molars is an orthodontic problem of major difficulty. When conventional appliances are used, the extrusion of adjacent teeth is likely. However, in recent years, temporary anchorage devices have been used to avoid unwanted side effects. For this purpose, mini-implants have primarily been inserted in the alveolar process. However, due to many disadvantages associated with mini-implant placement between the roots of the upper molars, it is now preferred to insert miniimplants in the anterior palate, which ensures a low risk of failure or mini-implant fracture.